2016
DOI: 10.1682/jrrd.2015.08.0151
|View full text |Cite
|
Sign up to set email alerts
|

Iraq/Afghanistan-era Veterans with back pain: Characteristics and predictors of compensation and pension award

Abstract: Abstract-Approximately 440,000 U.S. Veterans receive compensation for back and/or neck conditions. Veterans Benefits Administration (VBA) criteria state that back compensation determinations are based on impaired back function and not comorbidity or lifestyle, but whether compensation is based solely on consideration of the lumbosacral region is unknown. In this study, we conducted a cross-sectional analysis of medical chart data from 178 post-9/11 Veterans applying for service connection for back pain in fisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For example, our studies' participating veterans' overall pain severity (mean pain over the past week of 5.1) was higher than average NRS ratings from the MSD Cohort Study veterans, whose mean pain NRS scores were 3.4 in 2011 [61]. We are only aware of one other published study describing veterans seeking service connection for MSD, which also found high rates of pain-related impairment, substance use, and psychiatric comorbidity [62].…”
Section: Discussionmentioning
confidence: 69%
“…For example, our studies' participating veterans' overall pain severity (mean pain over the past week of 5.1) was higher than average NRS ratings from the MSD Cohort Study veterans, whose mean pain NRS scores were 3.4 in 2011 [61]. We are only aware of one other published study describing veterans seeking service connection for MSD, which also found high rates of pain-related impairment, substance use, and psychiatric comorbidity [62].…”
Section: Discussionmentioning
confidence: 69%
“…[ 15 ] Comorbid conditions are common; in a previously-described cohort of post-9/11 veterans seeking an initial service connection evaluation for back pain, the mean service connection rating was 14% for musculoskeletal disorders but averaged an additional 45% for other conditions. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…[15] Comorbid conditions are common; in a previously-described cohort of post-9/11 veterans seeking an initial service connection evaluation for back pain, the mean service connection rating was 14% for musculoskeletal disorders but averaged an additional 45% for other conditions. [16] The purpose of this study was to compare attitudes and beliefs about the service connection process between veterans submitting service connection claims for PTSD and musculoskeletal disorders. Examining and understanding attitudes towards the C&P process is important, as it can impact clinical care and engagement in treatment.…”
Section: Introductionmentioning
confidence: 99%